Pengaruh Penggunaan Media Story Stones terhadap Kemampuan Bahasa Ekspresif Lisan Anak Usia 4-5 Tahun di TK Gracia Sustain - Nia Devianna Laura Br Tarigan; Srinahyanti Srinahyanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Expressive language skills in children aged 4-5 years still face various problems that are not in accordance with their developmental stage, such as composing short sentences (children say